2021
DOI: 10.3389/fnut.2021.788929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Syringic Acid on Apoptosis, Inflammation, and AKT/mTOR Signaling Pathway in Gastric Cancer Cells

Abstract: Gastric cancer is one of the most common cancer and deadly disease worldwide. Despite substantial advances made in the treatment of gastric cancer, existing therapies still encounter bottlenecks. Chemotherapy, for instance, could lead to serious side effects, high drug resistance and treatment failure. Phytochemical-derived compounds from plants offer novel strategies as potent drug molecules in cancer therapy. Given the low toxicity and higher tolerance rate of naturally occurring compounds, the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The anti-inflammatory action of SACI was demonstrated by the significant decrease in testicular and hepatic COX-2 levels, which can be attributed to the inhibition of NF-κB activation, as discussed earlier. This finding is consistent with the work of Pei et al [ 59 ], who reported the anti-inflammatory action of SACI in gastric cancer cells by reducing the expressions of IL-6, NF-κB, TNF-α, and COX-2. In the liver of rats, the effect of SACI treatments on MCEL-induced elevation in COX-2 protein is dose-dependent, while the opposite is observed in the testis.…”
Section: Discussionsupporting
confidence: 93%
“…The anti-inflammatory action of SACI was demonstrated by the significant decrease in testicular and hepatic COX-2 levels, which can be attributed to the inhibition of NF-κB activation, as discussed earlier. This finding is consistent with the work of Pei et al [ 59 ], who reported the anti-inflammatory action of SACI in gastric cancer cells by reducing the expressions of IL-6, NF-κB, TNF-α, and COX-2. In the liver of rats, the effect of SACI treatments on MCEL-induced elevation in COX-2 protein is dose-dependent, while the opposite is observed in the testis.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, assembling both of them together by the cocrystallization technique is expected to augment OA’s permeability, which is exactly what is needed to address the poor permeability of OA as a BDDCS class-III drug, and even also lays a solid foundation for perfecting in vivo pharmacokinetic characteristics. Importantly, HSA possesses a diversity of biological activities that may confer beneficial effects on human health. ,,, Especially worth mentioning is that HSA, as an adjuvant antimicrobial ingredient, can exhibit antimicrobial abilities against multiple Gram-positive and Gram-negative bacteria through disparate mechanisms, ,, which renders a possible synergistic enhancement of the antimicrobial efficacy by cocrystallizing it with OA. Overall, it is the characteristic structural feature, favorable permeability, and appropriate antimicrobial ability that drive us to explore the directional self-assembly of HSA with OA into the target salt cocrystal, which not only provides a cocrystallization tactic of double optimization and synergistic enhancement efficacy but also fulfills a breakthrough in developing new salt cocrystals with synergistic antibacterial effects.…”
Section: Resultsmentioning
confidence: 99%
“…E. hirta extract is a promising source for arthritis by down regulating the levels of inflammatory mediators and up regulating the cytokines involved in antiinflammation [51], and possessed anti-inflammatory effects on neonatal asthmatic rats with inflammation [52]. Basu et al reported that E. bicolor latex extract markedly decreased orofacial mechanical allodynia in rats via reduction in ROS, and proinflammatory cytokines [53]. Upadhyay et al published that E. hirta methanolic down regulated the pro-inflammatory cytokine production in RAW246.7 macrophages and possessed a significant anti-inflammatory effect both in vitro and in vivo [54].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%